Parental Support and Future Orientation as Predictors of Career Decision-Making Among High School Students: A Correlational Study - Elvia Kurniawati; Zadrian Ardi; Daharnis Daharnis; Putra Suharnadi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Career decision making is a key developmental task in adolescence. However, many high school students struggle with indecision due to limited external support and underdeveloped internal motivation. This study explores the relationship between parental support, future orientation, and career decision making, focusing on their individual and combined influence. A descriptive correlational design was used involving 122 eleventh-grade students from Adabiah 2 High School in Padang, Indonesia, selected via stratified random sampling. Data were collected using validated Likert-scale questionnaires measuring parental support, future orientation, and career decision making. Analyses included simple and multiple regression, as well as multicollinearity diagnostics. Parental support (β = 0.834, R² = 0.694) and future orientation (β = 0.937, R² = 0.879) were both significant predictors of career decision making. However, in the combined model, only future orientation remained a significant predictor (β = 1.017, p .001), while parental support became non-significant. Multicollinearity tests showed high shared variance between predictors (VIF = 5.658), indicating conceptual overlap. The findings suggest that future orientation is a direct driver of career decision making, while parental support likely influences it indirectly by fostering future-oriented thinking. Schools should implement future-planning modules in counseling programs, and structured parental involvement should be encouraged. These results highlight the need to strengthen both internal capacities and external support to promote confident career choices in adolescents.